BIOGEOGRAPHY OF NITRARIA L. (Journal of Geography and Environmental Management, 2017)
Nitraria is a halophyte shrub, which grows in arid, semi-arid areas and particularly in saline deserts and salt marshes. The genus belongs to family Nitrariaceae and includes 10(12) species all over the world with unusual disjointed distribution. These shrubs are used in the protective afforestation for enhancing sand deposits and banks and reducing soil salinity and concentration of organic substances. The genus Nitraria L. is an old, Teritary Period’s relict plant which initially was described in Komarov’s investigations and given main hypothesis about its origin and distribution centers in Chinese and Mongolian floristic geography. The probability that Nitraria L. is a very antient genus, having its origins in Central Asia, is found as a theme of discussion of many researchers. The wide separateness between N. billardieri in Australia and the closely related N. schoberi in Eastern Europe and Asia has been difficult to explain. Recent molecular phylogenetic studies and methods have given new findings on systematics of the genus and new hypotheses on distribution pattern and time of origin. In this article, we discuss hypotheses about origin and distribution of Nitraria L.